Learning outcomes based assessment in distance higher education. A case study. (3rd April 2022) - Gil-Jaurena, Inés; Domínguez-Figaredo, Daniel; Ballesteros-Velázquez, Belén
ABSTRACT: This study focuses on an analysis of assessment methods according to expected learning outcomes in courses taught at the Universidad Nacional de Educación a Distancia (UNED) in Spain. Based on the European Higher Education Area and its learning-centred approach, the TALOE webtool has been used to analyse the internal coherence of 10 Bachelor's and Master's courses. The TALOE tool was developed in a European project and is free and publically available. The article gives a detailed explanation of how the courses' analysis has been carried out. The results indicate that, in general, the courses analysed are internally coherent. Nevertheless, we do indicate the mismatches in both the way the learning outcomes are written and the choice of assessment methods, conditioned by the mass character of certain courses. Finally, we give an example of improvements made in a course and we evaluate the utility of the TALOE tool in course design.